Population Dynamics of Cypripedium macranthos Sw. and Its Interactions with Environmental Factors in the Changbai Mountains - Lifei Chen; Wei Liu; Nan Jiang; Yiting Xiao; Yuze Shan; Shizhuo Wang; Sulei Wu; Qi Wang; Jiahui Yu; Yuqing Zhang; Xi Lu; Hongyu Qiao (Agronomy)
The growth and development of Cypripedium macranthos Sw. are affected by environmental factors, such as temperature, humidity, soil type, and its crown density. In this study, its morphological attributes, physiological traits, and interactions with environmental factors were analysed. The results indicate that the growth of C. macranthos was limited by elevated crown density, soil alkaline-hydrolysed nitrogen, and available soil potassium concentration. Moreover, the physiological attributes of C. macranthos were variably suppressed by high crown density and elevated soil alkaline-hydrolysed nitrogen concentration, whereas enhanced available soil potassium concentration promoted these physiological characteristics. At lower crown density, C. macranthos had greater photosynthetic capacity and higher δ13C, C, and N, which were more favourable for organic matter accumulation and plant growth and development. Conversely, at higher crown densities, plants relied more heavily on mycorrhizal fungi for nutrient acquisition. In conclusion, crown density, soil alkali-hydrolysed nitrogen, and available soil potassium concentration were the main environmental factors influencing the morphological and functional form of C. macranthos. Optimal growth conditions were identified at a crown density of 0.5–0.7, soil alkali-hydrolysed nitrogen concentration of 155.06–246.98 mg/kg, and available potassium concentration of 432.53–502.87 mg/kg. The results of this study provide a theoretical understanding for developing conservation strategies for C. macranthos to ensure the stability of the wild population and the health of its habitats.